Meat production traits of local Karayaka sheep in Turkey 1. The meat quality characteristic of lambs - Y. AKSOY; Z. ULUTAS (Chiriotti Editori, 2016)
This study is an investigation into the meat quality parameters of Karayaka lambs at different slaughter weights (SWs). The single-born Karayaka male lambs (n=30) selected for this study were an average live-weight of 20 kg and weaned at 2.5-3 months of age. The animals with pre-specified SWs were divided into slaughter weight (SW) groups (30, 35, 40, 45 and 50 kg) using a fully randomized design. To determine the M. longissimus dorsi et thoracis (LD) muscle meat quality characteristics, six lambs from each weight group were slaughtered. Results revealed significant differences among the slaughter groups with regard to pH, color parameters (L*-lightness, a*-redness, b* -yellowness), cooking loss (CL), drip loss (DL), moisture (M), crude protein (CP) and intramuscular fat (IF) ratios. Increasing water holding capacities (WHCs) and hardness values were observed with increasing SW. Significant differences were also observed among the slaughter groups with regard to total monounsaturated fatty acid + total polyunsaturated fatty acid/total saturated fatty acid ratios and total cholesterol content.